Cry freedom - Attenborough, Richard, 1923-2014 (California Universal Home Video, 1999)
Donald Woods is chief editor of the liberal newspaper Daily Dispatch in South Africa. He has written several editorials critical of the views of Steve Biko. But after having met him for the first time, he changes his opinion. They meet several times, and this means that Woods and his family get attention from the security police. When Steve Biko dies in police custody, he writes a book about Biko. The only way to get it published is for Woods himself to illegally escape the country.
Narra la historia en Sudáfrica del activista negro Stephen Biko y el redactor de un periódico liberal blanco que arriesga su propia vida para hacer llegar al mundo el mensaje de Biko
Reino Unido, 1987
Basada en libro "Biko" y "Asking for trouble" de Donald Woods
Kevin Kline, Penelope Wilton, Denzel Washington, John Thaw, Kevin McNally, Timothy West, Josette Simon, Wabei Siyolwe, John Matshikiza
No recomendada para menores de 13 años
Se tiene que ver en ordenador con el programa VLC media player
Lengua inglesa con subtítulos en español e inglés
Keywords: Películas cinematográficas -- DVD